PENGARUH PENAMBAHAN EKSTRAK BUAH LERAK (Sapindus rarak) PADA RANSUM YANG MENGANDUNG ASAM LEMAK OMEGA-3 TERHADAP PERFORMAN DAN PERLEMAKAN AYAM BROILER - , RAHMA KHALIFATUL JANNAH; , Dr. Ir. Supadmo. MS. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted to determine the effect of Lerak fruit (Sapindus rarak) extraction as feed additives on performance and fatness (abdominal fat, subcutaneous fat, and meat fat) of broilers which were fed with basal diet contained omega-3 fatty acid. Sixty male broiler chickens Lohmann strain of 7 days old were randomly divided in to four groups of treatment R0, R1, R2, and R3. R0 was raised without saponin while R1, R2, and R3 were given Lerak fruit extract as saponin source with different levels 0, 0.1, 0.3 and 0.5% of saponin. Each treatment consisted of three replications of five chickens each. Data of productivity performance (Feed Intake, Average Daily Gain, and Feed Conversion Ratio) and fatness were analyzed using one way of completely randomised design, followed by DMRT. The results showed that the treatments using saponin from Lerak fruit extraction up to 0.5% has no negative effect to the performance of broilers. The addition of 0.1% Sapindus rarak fruit extract decreased fatty meat of thighs percentage (P<0.05).